NAIGO: An Improved Method to Align PPI Networks Based on Gene Ontology and Graphlets - Zhu, Lijuan; Zhang, Ju; Zhang, Yi; Lang, Jidong; Xiang, Ju; Bai, Xiaogang; Yan, Na; Tian, Geng; Zhang, Huajun; Yang, Jialiang (Frontiers in Bioengineering and Biotechnology, 2020)
With the development of high throughput technologies, there are more and more protein-protein interaction (PPI) networks available, which provide a need for efficient computational tools for network alignment. Network alignment is widely used to predict functions of certain proteins, identify conserved network modules, and study the evolutionary relationship across species or biological entities. However, network alignment is an NP-complete problem and previous algorithms are usually slow or less accurate in aligning big networks like human versus yeast. In this study, we proposed a fast yet accurate algorithm called Network Alignment by Integrating Biological Process (NAIGO). Specifically, we first divided the networks into subnets taking the advantage of known prior knowledge, such as gene ontology. For each subnet pair, we then developed a novel method to align them by considering both protein orthologous information and their local structural information. After that, we expanded the obtained local network alignments in a greedy manner. Taking the aligned pairs as seeds, we formulated the global network alignment problem as an assignment problem based on similarity matrix, which was solved by the Hungarian method. We applied NAIGO to align Human and Saccharomyces cerevisiae S288c PPI network and compared the results with other popular methods like IsoRank, GRAAL, SANA and NABEECO. As a result, our method outperformed the competitors by aligning more orthologous proteins or matched interactions. In addition, we found a few potential functional orthologous proteins such as RRM2B in human and DNA2 in Saccharomyces cerevisiae S288c, which are related to DNA repair. We also identified a conserved subnet with six orthologous proteins EXO1, MSH3, MSH2, MLH1, MLH3 and MSH6, and six aligned interactions. All these proteins are associated with Mismatch repair. Finally, we predicted a few proteins of Saccharomyces cerevisiae S288c potentially involving in certain biological processes like Autophagosome assembly.